Socio-demographic factors and divorce among young married couples - A socio-cultural perspective - Ravindran, Anuja (Asian Journal of Interdisciplinary Research, 2021)
Divorce leads to many conflicts as women being single at an early age. This study aimed to determine the rate and socio-demographic associations of Divorce in Sri Lanka. A larger range of remarriages have conjointly additional to the increased numbers of marriages per annum. The data were gathered through an in-depth interview method and Questionnaire from 60 divorced young couples, to ignore the data duplication, data were collected from one of the divorced young couples who live in Batticaloa District, Sri Lanka. The research findings demonstrated that to reverse this trend, elders of the couple recommend and instruct them about the realities of life. Compromises and sacrifices are important aspects that the couple ought to have a secure married life.